2020
DOI: 10.1111/jfpe.13525
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an oscillating magnetic field on ice nucleation in aqueous iron‐oxide nanoparticle dispersions during supercooling and preservation of beef as a food application

Abstract: This study was aimed to explore the effects of an oscillating magnetic field (OMF) on the ice nucleation behavior of distilled water (DW) and iron‐oxide nanoparticle dispersion (IND) during supercooling. The magnetic field intensity and distribution of the OMF produced by Helmholtz coils were predicted using COMSOL. It was hypothesized that the ferric nanoparticles in the IND would promote the heterogeneous ice nucleation, and the OMF could inhibit the nucleation process by rotating the particles. The supercoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 38 publications
0
5
0
1
Order By: Relevance
“…A Gauss/Tesla meter (CH-1600, CH-Hall Electronic Devices Inc., China) was used to measure the intensity of the oscillating magnetic eld, with an accuracy of ± 0.2%. Helmholtz coil can generate a uniform magnetic eld in the central region (Hurtado-Velasco & Gonzalez-Llorente, 2016) and obtain an approximately cubic, homogeneous area at the center (Kang et al, 2020). Figure 1(b) illustrates three speci c test points using the Tesla meter in this experiment.…”
Section: Methodsmentioning
confidence: 99%
“…A Gauss/Tesla meter (CH-1600, CH-Hall Electronic Devices Inc., China) was used to measure the intensity of the oscillating magnetic eld, with an accuracy of ± 0.2%. Helmholtz coil can generate a uniform magnetic eld in the central region (Hurtado-Velasco & Gonzalez-Llorente, 2016) and obtain an approximately cubic, homogeneous area at the center (Kang et al, 2020). Figure 1(b) illustrates three speci c test points using the Tesla meter in this experiment.…”
Section: Methodsmentioning
confidence: 99%
“…A study by Kang at al. [ 137 ] found that fresh beef stored under refrigeration at −4 °C using an oscillating magnetic field was preserved for one week longer, without significant changes in weight loss, color or bacterial growth.…”
Section: Application Of Iron Nanoparticle-based Materials In Food Pro...mentioning
confidence: 99%
“…Experiments investigating the effects of electric field (EF)‐ and/or magnetic field (MF)‐assisted freezing on the size, quantity, and distribution of food ice crystals and the underlying mechanism have been widely reported (Alahakoon et al., 2016; Bhat et al., 2019; Kang et al., 2020; Mok et al., 2015). EFs have a significant influence on the freezing process based on theories such as dielectric breakdown and redirection of the water dipole.…”
Section: Approaches For Controlling Ice Crystal Growthmentioning
confidence: 99%
“…During the freezing process, the samples are in contact with the cold medium, which leads to a temperature gradient in the product with the phase change (water crystallization) until reaching thermal equilibrium. There are a variety of studies on inhibiting nucleation, regulating ice growth, and shortening the freezing time (Banerjee & Maheswarappa, 2019; Betoret et al., 2017; Biggs et al., 2019; Cheng et al., 2017a; Chow et al., 2003; Elfalleh et al., 2015; Farouk et al., 2004; Kang et al., 2020). To overcome the disadvantages of the widely used freezing methods (e.g., the air blast technique, immersion freezing, and spray freezing), novel technologies including high‐pressure freezing (HPF), ultrasound‐assisted freezing (UAF), electric field (EF) technology, and the use of antifreeze proteins (AFPs) have been developed (Cheng et al., 2017b; James et al., 2015).…”
Section: Introductionmentioning
confidence: 99%